Making paradigms of verbs and adjectives using a dialect corpus - Fukushima, Chitsuko (Slavia Centralis, 2020)
The author has been involved in the making of a dialect dictionary of Tokunoshima, Amami, Japan, using a dialect corpus. The analysis of the dialect corpus and face-to-face interviews were combined to obtain the paradigms of verbs and adjectives to be included in the multimedia dialect dictionary. Sentences in the corpus were cut into phrases and verbs were identified and sorted into lists of verbs. The lists were examined to find patterns of verb conjugation. All conjugated forms were examined regarding succeeding forms, and, based on the distribution, a conjugated form was chosen as an entry. In Japanese, verbs and adjectives belong to the same syntactic category and adjectives change their forms as verbs do. Thus the same procedure was repeated concerning adjectives, and patterns and paradigms of adjective inflection were found.